“What is Neoplatonism? Genesis and Crossroads of a Historical Category” - Zamora Calvo, José María (2025)
“What is Neoplatonism? Genesis and Crossroads of a Historical Category”. Within the context of philosophical historiography, the use of the term “Neoplatonism” to refer to the philosophy of Plotinus and his followers is relatively recent. In fact, it was first introduced in 1742 under the influence of Jacob Brucker. Between 1770 and 1790, the concept was utilized to distinguish this philosophical movement from Plato’s philosophy, emphasizing Neoplatonism’s incorporation of “eclecticism” and “sectarianism”, as well as its consequent divergence from Ancient Platonism. This paper aims to discuss the origin of the term “Neoplatonism” in relation to the philosophical movement that seeks the One as the unique and transcendent source of all reality. The transformation experienced by Platonism resulted from the equation between the One of the second part of the Parmenides and the Good of the 6th Book of the Republic.